A new methodology for the assessment of the running resistance of trains without knowing the characteristics of the track: Application to full-scale experimental data. (July 2018) - Somaschini, Claudio; Argentini, Tommaso; Rocchi, Daniele; Schito, Paolo; Tomasini, Gisella
The resistance to motion of trains is an essential requisite especially while designing high-speed trains and high-capacity railway lines. The optimisation of friction effects and aerodynamic performance can be done during the design stage of a new train but the actual value of the running resistance can be inferred only by means of full-scale tests during the operation of a train. A CEN standard (EN 14067-4) describes the methodologies for the assessment of the running resistance of railway vehicles starting from full-scale test measurements. According to this standard, the speed-dependent terms of the resistance force have to be determined by means of coasting tests on railway lines, whose characteristics must be well known. Since this is not always possible and small errors on the gradient could lead to major uncertainties in the evaluation of the resistance force, a new method for the estimation of the running resistance coefficients, irrespective of the characteristics of the track is proposed in this paper. The reliability of the method is verified by comparing the results with those obtained from the procedure proposed in the CEN standard. The comparison shows that the new methodology is able to evaluate the resistance coefficients with an accuracy equivalent to that of the other methods but with fewer tests and with a more robust procedure relying on a lesser number of parameters.